2011
DOI: 10.1073/pnas.1018653108
|View full text |Cite
|
Sign up to set email alerts
|

Clustering to identify RNA conformations constrained by secondary structure

Abstract: RNA often folds hierarchically, so that its sequence defines its secondary structure (helical base-paired regions connected by single-stranded junctions), which subsequently defines its tertiary fold. To preserve base-pairing and chain connectivity, the threedimensional conformations that RNA can explore are strongly confined compared to when secondary structure constraints are not enforced. Using three examples, we studied how secondary structure confines and dictates an RNA's preferred conformations. We made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…For the 5'-UTR of the mRNA GFP , we chose a conformation (C1) shown to produce the intended repression (6). Then, our algorithm explored all possible sequences compatible with such specifications (31,37), searching a stable hybridization of the two RNAs where the RBS remained unpaired. …”
Section: Resultsmentioning
confidence: 99%
“…For the 5'-UTR of the mRNA GFP , we chose a conformation (C1) shown to produce the intended repression (6). Then, our algorithm explored all possible sequences compatible with such specifications (31,37), searching a stable hybridization of the two RNAs where the RBS remained unpaired. …”
Section: Resultsmentioning
confidence: 99%
“…For example, theoretical work of a model two-helix junction has demonstrated that inter-helical dynamics strongly discriminate against the formation of tertiary contacts between some helical faces but allow others (Figure 8C) (129). Subsequent studies have since suggested that this property of inter-helical dynamics is broadly used by RNAs to encode their native folds (49, 128, 177179). Importantly, such a strategy may be how RNAs are able to overcome the limited information content of tertiary interactions, some of which like A-minor motifs appear to have little sequence specificity (180, 181).…”
Section: Interdependence Of Substates Across Tiersmentioning
confidence: 99%
“…Just as the position of 1 nt relative to the previous can be expressed as a function of the torsion angles and sugar pucker, the position of one coarse-grain helix relative to the previous can be expressed using a set of six different parameters (subsequently referred to as interhelical parameters) (Bailor et al 2011;Sim and The labels in black are names given to distinguish the different secondary structure elements in the graph. The elements f1 and t1 are the 5 ′ and 3 ′ unpaired regions, respectively.…”
Section: Proposal Distribution Model Building and Samplingmentioning
confidence: 99%